Comparative mammalian hazards of neonicotinoid insecticides among exposure durations - Zhen Wang; Bryan W. Brooks; Eddy Y. Zeng; Jing You (Environment International, 2019)
Neonicotinoid insecticides have become one of the most widely used insecticides over the past two decades. Recent studies have shown considerable risk of neonicotinoids to beneficial insects, however, their health risks to mammals are still under debate. Limited empirical mammalian toxicity information for neonicotinoids inherently presents challenges to environmental health practitioners performing health hazard and risk assessment. Therefore, we first compiled and examined publicly available hazard data for neonicotinoids, and knowledge gaps on mammals were identified. Probabilistic hazard assessment using chemical toxicity distributions (CTDs) was subsequently conducted, and initial thresholds of toxicological concern were derived for rat, dog, mouse, and rabbit under comparative experimental scenarios. Using the rat model, for example, oral 5% threshold concentrations (TC5s) of 0.11 (0.02, 0.36) and 0.23 (0.001, 3.2) mg/kg bw/day were estimated using chronic developmental and reproductive no observed adverse effect levels (NOAELs), respectively, while acute TC5 of 0.71 (0.25, 1.6) mg/kg bw/day was identified using neurological NOAELs. Comparatively, dermal and inhalational TC5s were estimated as 1583 (1172, 1777) and 451 (294, 615) mg/kg bw/day (equivalent to 486 (322, 622) mg/m3), respectively, using acute median lethal doses. Uncertainty factors (UFs) were also estimated using both CTD comparisons and individual UF probability distribution approaches to test whether rodent oral toxicity information or default 10-fold UF approach can provide sufficient protection for mammals. These initially identified UFs were generally smaller than default values (e.g., 10) employed by regulatory stakeholders, yet larger UFs were occasionally noted. Our findings appear particularly useful for environmental health practitioners when conducting screening-level risk assessment for neonicotinoids, and provide an example for health hazard assessment of pesticides with limited toxicity information. Keywords: Neonicotinoids, Chemical toxicity distribution, Threshold of toxicological concern, Uncertainty factor, Probabilistic health hazard assessment